Pengaruh Struktur Modal, Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan (Studi Pada Perusahaan Properti dan Real Estate Di Bursa Efek Indonesia tahun 2010-2012) - Novri Werti, Dola; Ramayani, S.Pd, ME,, Citra; Afriza, M.Pd, Rina (Pendidikan Ekonomi, 2014)
ABSTRACTÂ Issues that are examined in this study is the effect of capital structure , profitability , and firm size on firm value . The purpose of this study was to analyze the effect of capital structure , profitability , and firm size on firm value .The type of research is descriptive and associative . The population of this entire property and real estate companies listed on the Indonesia Stock Exchange totaling 45 companies . The sampling technique specified by purposive sampling so as to 27 companies that will be sampled . The data used in this study is a secondary data . Dependent variable and the independent variable value of the company s capital structure , profitability and firm size . The analysis model is a multiple linear regression analysis .Results obtained from testing the hypothesis that : First , capital structure does not significantly influence the value of the company with sig 0.539 > Î± = 0.05 . Second , profitability significantly influence the value of the company with sig 0.001 < Î± = 0.05 . Third , firm size significantly influence the value of the company with sig 0.008 < Î± = 0.05 . Fourth , capital structure , profitability and firm size significantly influence the value of the company with sig 0.001 < Î± = 0.05 .Based on the research results , the researchers suggest the company 1. Order to maintain its capital structure in order to give effect to the value of the company. 2. Order to continue to improve profitability by increasing profits that will affect the profitability of the increase in value of the company . In addition the company also must keep the asset because the asset will increase the value of the total assets of the ions so the size of the company will be high which will give a positive effect on firm value .